Diameter and Thickness Effects Scaling Deviations of High Explosives - Partom, Y (European Journal of Applied Sciences, 2023)
One way to characterize the sensitivity (or the reaction rate) of explosives is through size-effect tests. For explosive rods they are called diameter effect tests, and for explosive plates, they are called thickness effect tests. With high reaction rate explosives, different test configurations usually yield almost the same reaction rate or detonation velocity. But with low reaction rate explosives, different test configurations usually yield somewhat different detonation velocities. Following one of our previous papers [1], we propose here that those different detonation velocities result from the phenomenon of partially reacted boundary layers, that form when a detonation wave is grazing along a free boundary. In what follows we perform computer simulations to show how such a phenomenon comes about.